The predictive value of the FAPE-College Entrance Test (CET) for science and engineering freshmen of a provincial university - Ybanez, Lydia (Monzon) 1920-
This is an analysis of the predictive value of the FAPE-CET for the initial success of students who continued steadily in a science or in an engineering curriculum until their fourth semester in college. This is limited to discovering whether a freshman applicant may be more efficiently advised concerning his possible success in either curriculum, the decision being based on his scores on the CET subtests with Mathematics, Science and English as predictor variables.